2021
DOI: 10.3390/nu13061923
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lifestyle and Dietary Habits during COVID-19 Lockdown in Italy: Results of an Online Survey

Abstract: COVID-19 is an unprecedented global pandemic. On 12 March 2020, a lockdown order was issued in Italy in attempt to contain the health crisis. The study aimed to assess the impact of the COVID-19 lockdown on diet, physical activity, sleep quality, and distress in an Italian cohort. An online anonymous interview, which included validated questionnaires was created to compare lifestyle habits pre- and during the lockdown. Data analysis from 604 subjects with a mean age of 29.8 years was carried out using multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 75 publications
(103 reference statements)
3
32
0
3
Order By: Relevance
“…With regard to changes in food intake, increased consumption of fruit and vegetables was reported by 31 studies ( 20 , 22 , 25 , 27 , 29 , 32 , 33 , 35 , 45 , 49 , 52 , 54 , 60–63 , 65 , 71 , 76 , 83 , 87 , 89 , 90 , 92 , 94–96 , 103 , 111 , 113 ), whereas a decrease was found in 8 studies ( 59 , 73 , 77 , 82 , 86 , 91 , 99 , 110 ). However, some ( 4 , 26 , 81 ) found an increase only in vegetable consumption, as opposed to a decrease in fruit intake, while a French study ( 44 ) found a decrease in fresh fruit and vegetable consumption but an increase in canned and frozen vegetables.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to changes in food intake, increased consumption of fruit and vegetables was reported by 31 studies ( 20 , 22 , 25 , 27 , 29 , 32 , 33 , 35 , 45 , 49 , 52 , 54 , 60–63 , 65 , 71 , 76 , 83 , 87 , 89 , 90 , 92 , 94–96 , 103 , 111 , 113 ), whereas a decrease was found in 8 studies ( 59 , 73 , 77 , 82 , 86 , 91 , 99 , 110 ). However, some ( 4 , 26 , 81 ) found an increase only in vegetable consumption, as opposed to a decrease in fruit intake, while a French study ( 44 ) found a decrease in fresh fruit and vegetable consumption but an increase in canned and frozen vegetables.…”
Section: Resultsmentioning
confidence: 99%
“…Studies investigating cereal intake (e.g., pasta and rice, bread, flour, grains) reported an increased consumption of grains ( 4 , 22 , 25 , 29 , 35 , 41–43 , 45 , 62 , 77 , 81 , 86 , 89 , 99 ), and a lower intake of whole-grain products ( 65 , 77 , 99 ). A positive change was found in water consumption, which increased from 3.0% to 70.0% in all studies investigating this issue ( 23 , 25 , 41–44 , 62 , 68 , 77 , 78 , 86 , 89 , 104 , 113 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted during the COVID-19 pandemic have also reported some changes in eating behaviors. Several surveys reported an increase in snack consumption [17][18][19][20][21] and weight gain [18,19] during lockdown. A large Japanese study including the data of 5929 participants, 27.8% of whom were working from home, reported that those who started working from home during the COVID-19 pandemic increased their intake of vegetables, fruits, dairy products, and snacks and the consumption of self-made meals [20].…”
Section: Working From Home and Lifestyle Changesmentioning
confidence: 99%
“…During the pandemic, negative changes in eating habits and lifestyle such as increased consumption of alcohol, sweets, and fast food or reduced physical activity were reported [11,12]. Taking into account the positive aspects, an increased intake of fruits, vegetables, nuts, legumes, and fish was also observed [13].…”
Section: Introductionmentioning
confidence: 99%